Love of God and Neighbor: Living Charity in Aquinas’ Ethics - Clark, Meghan J. (New blackfriars, 2011)
The purpose of this paper is to examine the role of charity in the moral life by focusing on the nature of charity and its requirements. What does it mean to say that someone has charity? Through an examination of the virtue of charity: subject, object and order, I will establish the necessary way in which charity functions as love of neighbor, including the love of God through love of neighbor. Focusing then on love of neighbor, I will examine what, for Aquinas, is constitutive of living charity through mercy, beneficence and almsgiving. Throughout, I will argue that one cannot have charity without living charity through love of neighbor.